Mesenchymal Stromal Cells Rapidly Suppress TCR Signaling-Mediated Cytokine Transcription in Activated T Cells Through the ICAM-1/CD43 Interaction - Zheng, Shuwei; Huang, Ke; Xia, Wenjie; Shi, Jiahao; Liu, Qiuli; Zhang, Xiaoran; Li, Gang; Chen, Jieying; Wang, Tao; Chen, Xiaoyong; Xiang, Andy Peng (Frontiers in Immunology, 2021)
Cell-cell contact participates in the process of mesenchymal stem cell (MSC)-mediated T cell modulation and thus contributes to MSC-based therapies for various inflammatory diseases, especially T cell-mediated diseases. However, the mechanisms underlying the adhesion interactions between MSCs and T cells are still poorly understood. In this study, we explored the interaction between MSCs and T cells and found that activated T cells could rapidly adhere to MSCs, leading to significant reduction of TNF-α and IFN-γ mRNA expression. Furthermore, TCR-proximal signaling in activated T cells was also dramatically suppressed in the MSC co-culture, resulting in weakened Ca2+ signaling. MSCs rapidly suppressed TCR signaling and its downstream signaling in a cell-cell contact-dependent manner, partially through the ICAM-1/CD43 adhesion interaction. Blockade of either ICAM-1 on MSCs or CD43 on T cells significantly reversed this rapid suppression of proinflammatory cytokine expression in T cells. Mechanistically, MSC-derived ICAM-1 likely disrupts CD43-mediated TCR microcluster formation to limit T cell activation. Taken together, our results reveal a fast mechanism of activated T cell inhibition by MSC, which provides new clues to unravel the MSC-mediated immunoregulatory mechanism for aGVHD and other severe acute T cell-related diseases.